CLASSROOM MANAGEMENT FOR IMPROVING THE CHILDREN VALUES - Amalia, Rizka; Metroyadi, Metroyadi; Agusta, Akhmad Riandy; Halimatussadi’yah, Halimatussadi’yah (E-CHIEF Journal, 2023)
The research is motivated by low religious abilities, such as children being less able to express opinions in continuing some prayer movements. This is due to the lack of innovative and interesting learning media to be displayed, the lack of innovation in learning models and methods used, the lack of stimulus given by teachers to children in learning activities, and children being less able to express ideas in continuing some of the prayer movements they have heard. The approach used is a qualitative approach to the type of research, namely classroom action research, which is carried out in two cycles. This research was carried out at Tri Kesuma Pelaihari Kindergarten on group B children, totaling 10 children, consisting of 5 boys and 5 girls. Based on the research results, it can be concluded that using the talking stick model, demonstration method, and drawing media can develop religious abilities in Group B children at Tri Kesuma Kindergarten. It is recommended that the results of this research be used as a reference and consideration in continuing some of the prayer movements that have been carried out.